Mengelola Waktu Belajar dan Bekerja Dengan Bijak: Risiko dan Strategi Kuliah Sambil Bekerja - Laila Listiani Putri; Dina Nurkhaliza; Siti Ropiah; Sri Ayu Wulandari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Balancing study and work has become a significant challenge for vocational high school students, as managing academic responsibilities alongside part-time employment can lead to stress, fatigue, and reduced academic performance if not handled wisely. This community service program, titled “Managing Study and Work Time Wisely: Risks and Strategies for Studying While Working”, aimed to equip students with practical knowledge and strategies to manage their dual responsibilities effectively while raising awareness of potential risks associated with poor time management. The activity was conducted at SMK Perguruan Rakyat Jakarta on October 31, 2025, involving 16 facilitators, comprising students and lecturers from Universitas Pamulang, and 50 participating SMK students. The program was implemented in three stages: preparation, implementation, and reporting. In the preparation stage, facilitators developed materials on time management techniques, risk awareness, and prioritization strategies. During implementation, participants engaged in experience-sharing sessions, interactive discussions, and question-and-answer activities, fostering active participation and peer learning. The reporting stage summarized the outcomes, feedback, and reflections from both facilitators and students. The results indicated that students gained a better understanding of the risks of poor time management, improved awareness of strategies such as scheduling, prioritization, and self-reflection, and expressed motivation to apply these strategies in their daily academic and work routines. The program successfully enhanced students’ ability to balance study and work responsibly.